Tourism and air transport - an economic evaluation of the Oporto Airport expansion project - Vânia Natércia Gonçalves Costa (Tourism & Management Studies)
Over the past few years the rate of air transport use has increased, making it a crucial sector of activity in economic and tourism development. It has become essential to adapt airport infrastructures to the new requirements of demand. This study aims evaluate and quantify, in socio-economic terms, the impact of investment of an airport infrastructure expansion project. This research focused on a case study of the Oporto Airport, the investment in expanding the capacity of the entire airport infrastructure from three to 11 million passengers the expansion project of this airport, which ran from 2000 to 2007 and involved a total investment of €407 million. The methodology used is based on the economic evaluation, concretely applying the cost-benefit analysis method, which compares the social benefits and decision costs. According to the results obtained, the expansion project of Oporto Airport is expected to be a good investment from a socioeconomic viewpoint.